LOCAL INNOVATION SYSTEM IN WONOGIRI DISTRICT TO EMPOWER THE COMMUNITY THROUGH REGIONAL EXCELLENCE IN ASEAN ECONOMICS ERA - Rahmawati Rahmawati; Sri Murni; Siti Supeni (Universitas Negeri Semarang, 2018)
The acceleration of implementation, difusion, and innovation learning in all segments along with innovation outcomes in all segments will only take place when development planning that is integrated with local potency and excellence, which has competitiveness, and the availability of a comprehensive and accurate innovation data is exist. Sectoral paradigm along witha spatial and temporal development has to be revisited because the nature of development is human and environment as a whole (Santosa et al., 2012). The general purpose of this study is to formulate a model of local innovation system-sistem inovasi daerah (SIDa) of Wonogiri government. The approach to local development is done in systemic and systematic manner. Through this approach, all of the subjects, institutions, networks, partnerships, actions, production processes, and policies that affect the direction of development, velocity and difussion of innovation, and learning processed are considered in order to achieve the development of Wonogiri district. After the data collection, workshop, and Focus Group Discussion (FGD) is performed, then the draft of SIDa is ratified by the Regulation of Wonogiri Regent. The next steps are socialization and public examination.